PERAN KEPUASAN KONSUMEN MEMEDIASI PENGARUH KUALITASPELAYANAN TERHADAP REPURCHASE INTENTION DI TKD COFFEE &EATERY BALI - Anak Agung Sagung Shinta Kumaladewi; Putu Saroyini Piartrini (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the effect of service quality on repurchase intention mediated by customer satisfaction at TKD Coffee & Eatery Bali. The research is motivated by the sales fluctuations experienced by TKD Coffee & Eatery over the past three years, which are suspected to be caused by a decline in service quality. This is a quantitative causal associative study using path analysis and Sobel test. A total of 100 respondents were selected using the Slovin formula and were limited to consumers residing in Kesiman Village. The results show that: (1) service quality has a positive and significant effect on customer satisfaction, (2) service quality has a positive and significant effect on repurchase intention, (3) customer satisfaction has a positive and significant effect on repurchase intention, and (4) customer satisfaction partially mediates the effect of service quality on repurchase intention. These findings highlight the importance of improving service quality as a strategy to enhance customer satisfaction and increase repurchase intention. The study recommends performance evaluation and service training for staff to optimize customer satisfaction